Identification of Key Proteins in Human Epithelial Cells Responding to Bystander Signals From Irradiated Trout Skin. Issue 3 (24th July 2015) - Furlong, Hayley; Smith, Richard; Wang, Jiaxi; Seymour, Colin; Mothersill, Carmel; Howe, Orla
Radiation-induced bystander signaling has been found to occur in live rainbow trout fish ( Oncorhynchus mykiss ). This article reports identification of key proteomic changes in a bystander reporter cell line (HaCaT) grown in low-dose irradiated tissue-conditioned media (ITCM) from rainbow trout fish. In vitro explant cultures were generated from the skin of fish previously exposed to low doses (0.1 and 0.5 Gy) of X-ray radiation in vivo. The ITCM was harvested from all donor explant cultures and placed on recipient HaCaT cells to observe any change in protein expression caused by the bystander signals. Proteomic methods using 2-dimensional (2D) gel electrophoresis and mass spectroscopy were employed to screen for novel proteins expressed. The proteomic changes measured in HaCaT cells receiving the ITCM revealed that exposure to 0.5 Gy induced an upregulation of annexin A2 and cingulin and a downregulation of Rho-GDI2, F-actin-capping protein subunit beta, microtubule-associated protein RP/EB family member, and 14-3-3 proteins. The 0.1 Gy dose also induced a downregulation of Rho-GDI2, hMMS19, F-actin-capping protein subunit beta, and microtubule-associated protein RP/EB family member proteins. The proteins reported may influence apoptotic signaling, as the results were suggestive of an induction of cell communication, repair mechanisms, and dysregulation of growth signals.